Iowa Birdline update, November 28, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for November 28, 1994. Highlights of the update include sightings of a Black-headed Gull, a Red Phalarope, a Red-throated Loon, a Prairie Falcon, and a Snowy Owl. Also of note were observations of several species of Ducks, Grebes, and Swans. Also included are handwritten notes for the next week's update with sightings of a Thayer's Gull and a male Cinnamon Teal along with updates of previously seen birds. Epson - sheet feed/flatbed